(NmETODY STATISTI^ESKOGO OCENIWANIQ PARAMETROW SLU^AJNYH PROCESSOW (B/s - (NoGARKOW(B, (NmIHAIL aLEKSEEWI^s ((NmOSKWA (B:s (N|NERGOATOMIZDAT(B,s, 1990)
(NbIBLIOGR(B.: (NS(B. 200-205 (129 (NNAZW(B.)s
Keywords: (NsLU^AJNYE PROCESSY (B((NMAT(B.) - (NsTATISTI^ESKIE METODY IZU^ENIQs